2015
DOI: 10.1152/jn.00615.2014
|View full text |Cite
|
Sign up to set email alerts
|

Role of neuronal nitric oxide synthase in the estrogenic attenuation of cannabinoid-induced changes in energy homeostasis

Abstract: Since estradiol attenuates cannabinoid-induced increases in energy intake, energy expenditure, and transmission at proopiomelanocortin (POMC) synapses in the hypothalamic arcuate nucleus (ARC), we tested the hypothesis that neuronal nitric oxide synthase (nNOS) plays an integral role. To this end, whole animal experiments were carried out in gonadectomized female guinea pigs. Estradiol benzoate (EB; 10 μg sc) decreased incremental food intake as well as O2 consumption, CO2 production, and metabolic heat produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…Using an established treatment paradigm schematically represented by the timeline shown in Figure 1, we found that estradiol per se increased the expression of the PI3K p85α regulatory subunit in the ARC (Figure 2). Western blotting of ARC tissue microdissected from two to three 1mm-thick coronal slices spanning its rostral-caudal extent as described previously [4345] revealed clear phosphorylated Akt (pAkt) and total Akt bands measuring 60 KDa in weight (Figure 3). Estradiol administered two hours prior to tissue harvesting increased the amount of pAkt in the ARC compared to vehicle-treated controls (Figure 3).…”
Section: Introductionmentioning
confidence: 63%
“…Using an established treatment paradigm schematically represented by the timeline shown in Figure 1, we found that estradiol per se increased the expression of the PI3K p85α regulatory subunit in the ARC (Figure 2). Western blotting of ARC tissue microdissected from two to three 1mm-thick coronal slices spanning its rostral-caudal extent as described previously [4345] revealed clear phosphorylated Akt (pAkt) and total Akt bands measuring 60 KDa in weight (Figure 3). Estradiol administered two hours prior to tissue harvesting increased the amount of pAkt in the ARC compared to vehicle-treated controls (Figure 3).…”
Section: Introductionmentioning
confidence: 63%
“…This enzyme is also regulated by E 2 in the PVN, as is endothelial nitric oxide synthase (eNOS) in the vascular endothelium through an Src kinase (SRC)/PI3k/Akt pathway [43;44], and we have shown previously that E 2 increases nNOS activity in the ARH [37]. The nNOS enzyme stimulates guanylate cyclase, which will convert GTP to cGMP.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, there is compelling precedence for rapid estrogenic attenuation of metabotropic, G i/o -coupled receptors like the GABA B , μ-opioid and cannabinoid CB1 receptors from their effector systems. There is also a burgeoning yet incomplete understanding of the signaling molecules such as PLC, PKC, PKA and neuronal nitric oxide synthase (nNOS) through which this process takes place [36;37]. Moreover, recent evidence indicates that E 2 rapidly attenuates ORL-1 receptor-mediated antinociception via an ERK2-dependent mechanism [38].…”
Section: Introductionmentioning
confidence: 99%
“…Estradiol replacement in ovariectomized females reduces energy intake per se , and rapidly and markedly attenuates the increase in energy intake caused by WIN 55,212-2, and also reduces the magnitude and duration of the agonistinduced hypothermia (Kellert et al, 2009). Again, this can be drilled down to the level of the hypothalamic feeding circuitry, where estradiol rapidly diminishes the endocannabinoid-mediated, retrograde inhibition of glutamatergic input onto POMC neurons as assessed through depolarization-induced suppression of excitation (DSE), as well as the enhancement of the I A in these cells (Borgquist et al, 2015a; Kellert et al, 2009). …”
Section: Sex Differences In the Cannabinoid Regulation Of Energy Hmentioning
confidence: 99%
“…Activation of these receptors by estradiol elicits a signal transduction cascade involving phosphatidylinositol-3-kinase (PI3K), protein kinase C (PKC), protein kinase A (PKA) and neuronal nitric oxide synthase (nNOS) to unravel the coupling of the presynaptic CB1 receptors to their effector systems (Borgquist et al, 2015a; Mela et al, 2015; Washburn et al, 2013) (Figure 1). PI3K is a signaling molecule that is activated upon both ERα and ERβ stimulation (Gingerich and Krukoff, 2008; Smith et al, 2013), as well as by other anorexigenic hormones such as leptin and insulin (Hill et al, 2008; Mela et al, 2015; Qiu et al, 2014), within various elements of the hypothalamic feeding circuitry.…”
Section: Sex Differences In the Cannabinoid Regulation Of Energy Hmentioning
confidence: 99%